The effect of Azorhizobium caulinodans ORS571 and γ-aminobutyric acid on salt tolerance of Sesbania rostrata - Liu, Yanan; Liu, Xiaolin; Dong, Xiaoyan; Yan, Jiaming; Xie, Zhihong; Luo, Yongming (Frontiers in Plant Science, 2022)
Salt stress seriously affects plant growth and crop yield, and has become an important factor that threatens the soil quality worldwide. In recent years, the cultivation of salt-tolerant plants such as Sesbania rostrata has a positive effect on improving coastal saline-alkali land. Microbial inoculation and GABA addition have been shown to enhance the plant tolerance in response to the abiotic stresses, but studies in green manure crops and the revelation of related mechanisms are not clear. In this study, the effects of inoculation with Azorhizobium caulinodans ORS571 and exogenous addition of γ-Aminobutyric Acid (GABA; 200 mg·L−1) on the growth and development of S. rostrata under salt stress were investigated using potting experiments of vermiculite. The results showed that inoculation with ORS571 significantly increased the plant height, biomass, chlorophyll content, proline content (PRO), catalase (CAT) activity, and superoxide dismutase (SOD) activity of S. rostrata and reduced the malondialdehyde (MDA) level of leaves. The exogenous addition of GABA also increased the height, biomass, and CAT activity and reduced the MDA and PRO level of leaves. In addition, exogenous addition of GABA still had a certain improvement on the CAT activity and chlorophyll content of the ORS571-S. rostrata symbiotic system. In conclusion, ORS571 inoculation and GABA application have a positive effect on improving the salt stress tolerance in S. rostrata, which are closely associated with increasing chlorophyll synthesis and antioxidant enzyme activity and changing the amino acid content. Therefore, it can be used as a potential biological measure to improve the saline-alkali land.